Potential of Nanoparticulate Fertilizers in Mitigating Environmental Stresses - de Souza Júnior, Jonas Pereira; Costa, Milton Garcia [UNESP]; Oliveira, Kamilla Silva; Kadyampakeni, Davie; de Mello Prado, Renato [UNESP]; Tubana, Brenda S. (Springer Nature, 2025)
The growing interest in the application of nanofertilizers in agriculture has been attributed to their promising results in the alleviation of environmental stress in plants. Nanoparticles offer a novel approach to deliver essential and beneficial elements to plants optimizing their absorption and utilization. They can also be designed to release elements in a controlled manner, for steady supply of plant-available nutrients. Moreover, nanoparticles can protect the nutrients from undesirable interactions in the soil, which allow maximum uptake and use efficiency of nutrients. A vast amount of literature reports that nanofertilizers do not only combat nutritional deficiency but also enhance plant tolerance to other environmental stressors. Continued research in this area is vital to refine the action of nanofertilizers in terms of improving plant nutrition and raising crop productivity in a sustainable way. From this perspective, the current chapter explains how nanofertilizers could alleviate the influence of environmental stresses on crops and elucidate their practical applications in agriculture.